IMPROVEMENT OF SURVIVABILITY OF FIBER OPTIC COMMUNICATION SYSTEM USED FOR DATA TRANSMISSION IN EMERGENCIES - A. O. Zenevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Fiber optic communication system used for data transmission in emergencies has been suggested. It has been shown in this paper that for increasing survivability of such systems, optical radiation with a wavelength of 850 nm, photon counter and asynchronous data transfer mode are to be used.